Contributions of health process management and its impact on hospital management - Vizzoni , Alexandre Gomes; Ferreira , Paulo Henrique da Costa; Fagundes , Michael Jacob (Seven Editora, 2023)
The role of hospital manager is invariably complex, regardless of the region, in fact that, even in certain aspects, health services are more challenging in some countries, due to the regulation of beds, financing and technologies available. Added to the extensive list of managerial demands, the requirement for specific knowledge in the management of human and physical resources. The influence of the fragmented model of work organization, in which each professional performs portions of the work without an integration with the other areas involved, has been pointed out as one of the reasons that hinder the accomplishment of a more integrative and better quality health work, both from the perspective of those who perform it and for those who enjoy it. From  the moment that health professionals, who work directly with the patient, occupy coordinations, as they ascend in the organization, they begin to perform more administrative tasks. As an example, it is possible to notice that a nurse or doctor who coordinates an inpatient unit, perform more administrative functions and almost no technique. They use their technical expertise to act in the leadership. These professionals, when occupying certain positions, do not always understand the administrative activities. With this, the hospital loses a good technician and may not gain a good boss.  This paper has a reflective description about the hospital management process. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-102